Meningkatkan Pemahaman Konsep IPA Melalui Model Pembelajaran Problem Based Learning Siswa Kelas IV UPTD SPF SD Negeri Pulo Sarok Singkil - Syafriani, Reni; Hasanah, Hasanah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to improve understanding of science concepts through a problem-based learning model for Class IV UPTD SPF SD Negeri Pulo Sarok with a total of 21 students, 11 boys and 10 girls. The time of the research was carried out in November of the 2021 academic year. The research method used was classroom action research using a cycle model from Kemmis and Mc.Taggart with four stages ineach cycle, namely the planning, action implementation, observation and reflection stages. The instrument used in the form of student and teacher activity observation sheets. The results of the study by applying a problem-based learning model can improve students' understanding of science concepts. In the first cycle of the first meeting is 43.00% and the first cycle of the second meeting is 62.00%. The increase occurred in the second cycle of the first meeting of 81.00% and the second cycle of the second meeting of 95.00%. The percentage of teacher action monitoring data in the first cycle of the 1st meeting was 71.25% and the secondmeeting was 73.75%. In the second cycle, it increased to the first meeting of 88.75% and the second meeting of 95.00%. Meanwhile, the percentage of student action monitoring data in the first cycle of the 1st meeting was 68.75% and the second meeting was 72.50%. In the second cycle, it increased to the 1st meeting of 85.00% and the second meeting of 93.75%. Thus learning science using problem-based learning models canimprove students' understanding of science concepts. The implication of this research is that through the use of problem-based learning models in science learning, it can improve understanding of science concepts for fourth grade students of UPTD SPF SD Negeri Pulo Sarok Singkil.